PENERAPAN BIDANG FISIKA MELALUI BIMBINGAN TEKNIS PADA BANGUNAN GEDUNG BAGI SISWA SMAN 81 DAN SMAN 42 JAKARTA TIMUR - Endah Setyaningsih; Sigit Wijono (MADANI: Jurnal Pengabdian Kepada Masyarakat, 2018)
Abstract Physics subjects are considered difficult for some students, for that the teachers try to find methods to  convey physics subjects to be easily understood by students. One method is the practice in the laboratory or applying physical principles in everyday life. The implementation of subjects through practice in the laboratory and in the surrounding environment is one of the characteristics of the 2013 curriculum. Through this service to the community, activities that are applied in physics in daily life are carried out, namely about how to airconditioning (cooling) in a room. Here will be explained about heat transfer through conduction, radiation and convection. Another activity is to introduce various types of electric lamps that are energy-efficient and class-level lighting needs. The two examples of the application of physics are associated with the Indonesian National Standard (SNI), which is a reference value for comfortable conditions for the use of AC and the level of lighting in the classroom. The results of technical guidance activities by providing examples of the application of physics to buildings in the form of the use of lights and air conditioning and the use of measuring instruments make students interested in participating in activities. Thus students are expected to better understand the material presented.Activities related to energy saving are also in harmony with activities related to the environment such as those thathave been widely practiced in the school environment.